An Analysis of Ibn Taimmiyah's Hijā' in Qasīdah Lāmiyah as the Identity of the Mahdzab Hambali - Fauzi, Abi; Liza, Fitri (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2024)
This research aims to analyze the style of satire (hijā’) used by Ibn Taymiyyah in his book titled "Qasīdah Lāmiyah (The Satirical Poem)". It is a work by Ibn Taymiyyah that contains satirical poetry directed towards those who questioned his scholarly identity. Hijā’ style is poetry used to mock other poets in a distinctive manner, often in the form of self-praise or disparagement of a group. However, since the advent of Islam, this style has frequently been used to defend Islam, whether individuals or groups, including scholars like Ibn Taymiyyah. This research employs a qualitative approach using content analysis method. Content analysis, according to Creswell, is a qualitative research method used to identify specific patterns or themes within text. The analysis results indicate that verses of satirical poetry (shiʿr hijâ) were found in Qasīdah Lāmiyah, consisting of 2 types of ethical satire (al-hijâ al-akhlâqî) and 14 verses of religious satire (al-hijâ al-dînî).